2014
DOI: 10.1136/bcr-2014-203842
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous tubulointerstitial nephritis secondary to omeprazole

Abstract: Drug-induced interstitial nephritis is a common cause of acute kidney injury indicated by elevated serum creatinine. We report a case of omeprazole-induced acute granulomatous interstitial nephritis (GIN). Our patient developed acute GIN secondary to omeprazole ingestion requiring haemodialysis. Treatment with steroids and withdrawal of omperazole was successful allowing the patient to discontinue haemodialysis in 3 months. She remains dialysis free with chronic kidney disease stage IV, reflected by a serum cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…6 If granulomatous inflammation is present in a renal biopsy, the differential diagnosis include renal tuberculosis, renal sarcoidosis, drug-induced granulomatous interstitial nephritis, and tubulointerstitial nephritis and uveitis (TINU). 2 There are limited reports of GIN with NSAIDs; and antibiotics are presumed the most likely causative agents in our patient. Javaud et al found 7 out of 40 consecutive renal biopsies between January 1991 and February 2004 to have GIN that were considered druginduced.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…6 If granulomatous inflammation is present in a renal biopsy, the differential diagnosis include renal tuberculosis, renal sarcoidosis, drug-induced granulomatous interstitial nephritis, and tubulointerstitial nephritis and uveitis (TINU). 2 There are limited reports of GIN with NSAIDs; and antibiotics are presumed the most likely causative agents in our patient. Javaud et al found 7 out of 40 consecutive renal biopsies between January 1991 and February 2004 to have GIN that were considered druginduced.…”
Section: Discussionmentioning
confidence: 74%
“…Penicillins (ampicillin, oxacillin and methicillin) and cephalosporins have been linked to GIN in several case reports. 2,7 However, which of these two drugs was the culprit in our case, could not be determined as both can cause GIN as they share same histopathological patterns. When the cause of AKI remains unexplained, a renal biopsy is indicated for definitive diagnosis and management.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Patient 2 was receiving nitrofurantoin, and patient 5 was on lisinopril medications that were described in rare case reports to cause GIN [21,22]. However, the 2 patients had been on these medications for many years without side effects; therefore, it is unlikely that they were responsible for GIN.…”
Section: Discussionmentioning
confidence: 91%
“… 8 PPIs are prescribed to treat gastric diseases such as gastric and duodenal ulcers, gastroesophageal reflux disease, and erosive esophagitis. 9 …”
mentioning
confidence: 99%